RANDOMİZE KLİNİK DENEYLERİN DEĞERLENDİRİLMESİNDE BİR ÖLÇEK ÖNERİSİ - ÇAĞATAY, Penbe; ŞENOCAK, Mustafa; BAYKAL, İ. Engin (Cerrahpaşa Medical Journal, 2014)
Background.- Randomized controlled trials are generally regarded as the most scientific method in decision making for diagnosis and treatment. Therefore they must be far away from methodological and statistical mistakes, but it is know that there are inadequate points in these studies. A system of scoring parameters has been established to put forward the scientific quality of randomized controlled trials. It has been planned so that these parameters show the scientific reliability of the studies, evaluation of academic papers, inclusion for meta-analyses. Three criterions have been developed for scoring orders. This three criterion are: 1) 12 headlines for methodological and statistical main items (maximum 60 points); 2) 6 headlines for scientific research (maximum 24 points); 3) 6 headlines for secondary parameters in supervision and control (maximum 12 points). Our mean objective was to establish a scoring system to show the quality of the scientific literature according to their contents especially in randomized controlled trials. As a result, our scoring system will demonstrate all the specification of a scientific literature which has to contain also the future inclinations and the supplementing informations in itself so that an evaluation method will help determine the scientific level, acceptance of a paper, education of methodology for scientists working in this field and pursuit of developments.